Diagnosis of Infections Caused by Pathogenic Free-Living Amoebae - da Rocha-Azevedo, Bruno; Tanowitz, Herbert B.; Marciano-Cabral, Francine (Interdisciplinary Perspectives on Infectious Diseases, 2009)
Naegleria fowleri, Acanthamoeba spp., Balamuthia mandrillaris, and Sappinia sp. are pathogenic free-living amoebae. N. fowleri causes Primary Amoebic Meningoencephalitis, a rapidly fatal disease of the central nervous system, while Acanthamoeba spp. and B. mandrillaris cause chronic granulomatous encephalitis. Acanthamoeba spp. also can cause cutaneous lesions and Amoebic Keratitis, a sight-threatening infection of the cornea that is associated with contact lens use or corneal trauma. Sappinia pedata has been identified as the cause of a nonlethal case of amoebic encephalitis. In view of the potential health consequences due to infection with these amoebae, rapid diagnosis is critical for early treatment. Microscopic examination and culture of biopsy specimens, cerebral spinal fluid (CSF), and corneal scrapings have been used in the clinical laboratory. For amoebic keratitis, confocal microscopy has been used to successfully identify amoebae in corneal tissue. More recently, conventional and real-time PCR assays have been developed that are sensitive and specific for the amoebae. In addition, multiplex PCR assays are available for the rapid identification of these pathogens in biopsy tissue, CSF, and corneal specimens.